Cultivation Of Isochrysis Maritima Billard And Parke For Lipid Production Using Airlift Photobioreactor - Mustapha, Nik Farhana Nadiah Nik (2013)
Isochrysis maritima was cultivated in 4 L of airlift photobioreactor aiming for the production of high biomass, lipid and polyunsaturated fatty acid (PUFA)s production. Three types of cultivation modes have been applied to enhance the production of both biomass and lipid concentration which were photoautotrophic, heterotrophic and photoheterotrophic cultivation, employing two types of cultivation modification which were repeated-stage and two-stage cultivation strategy. The highest lipid productivity was achieved in photoheterotrophic cultivation condition which was 1.39 g/L/day with 6.03 g/L/day of biomass productivity. The achievement was approximately 15-fold higher than the concentration obtained from the photoautotrophic (0.17 g/L/day, 0.75 g/L/day). These outputs were accomplished with the combination of repeated-stage cultivation strategy at 156 μmol photon of light intensity. By using the combination, the lipid yield was found to be 3-fold higher (Yp/fruc = 0.18) than in the repeated-stage of heterotrophic cultivation condition (Yp/fruc= 0.06). The improving results obtained have indicated the effectiveness of light supplementation in the lipid production of Isochrysis maritima.